(1255) Energy planning in the Arab world تخطيط الطاقة في العالم العربي - Elshafei, Alwalid N. (معهد التخطيط القومي, 2018)
Over the last decade or SD, global and regional issues such as population growth, food shortage, and economic and social development have been the subject of substantial international research programmes. this effort has led to conceptualization of problems and possible solutions, as well as to the realization of the considerable difficulties involved.